Hubungan Personal Hygiene dengan Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Muara Dua Kota Lhokseumawe - Rosmiati Rosmiati; Mauliza Mauliza; Mardiati Mardiati (Pusat Riset dan Inovasi Nasional, 2025)
Diarrhea is a condition in which individuals experience 3 or more bowel movements per day with the consistency of liquid stools. Diarrhea causes death in children, accounting for around 9% of all deaths among children under 5 years of age worldwide in 2019. Diarrhea can be caused by a variety of bacteria, viruses, fungi and parasites. Diarrhea can occur due to poor personal hygiene. The purpose of this study was to determine the relationship between personal hygiene and the incidence of diarrhea in toddlers in the Working Area of ​​the Muara Dua Public Health Center, Lhokseumawe City. This research method uses a cross-sectional design, with respondents who have toddlers aged 12-59 months. The results of the study based on the characteristics of age, education, and occupation of mothers were mostly found at the age of 26-35 years with tertiary education and the most who did not work. The distribution of respondents toddlers based on age and sex was mostly found in toddlers aged 25-59 months and were female. The results of the study found that many toddlers had diarrhea. The results of the study using the chi square test showed that there was a relationship between the habit of washing hands with soap, the habit of using milk bottles, and the habit of keeping food equipment clean with the incidence of diarrhea in toddlers in the Working Area of ​​the Muara Dua Health Center, Lhokseumawe City with a p value <0.05. There was relationship between personal hygiene behavior and incidence of diarrhea in toddlers the Working Area of ​​the Muara Dua Health Center, Lhokseumawe City.